(untitled) (Journal of Information Technologies in Education (ITE), 2011)
The article describes experience of projection and developing of the system of web-sites of Melitopol’ State teachers training University named after Bohdan Khmel’nitskiy’s faculties: stages of projecting, generalrequirements and demands to functioning and design, structure, principles of content building of the developed information sources.